Facilitating Networks and Network Learning Through the Provision of a Human and IT-enabled Infrastructure - Burgoyne, John; Williams, Sadie (Proceedings of the International Conference on Networked Learning, 2004)
This paper presents a case study of a change and development initiative in the National Health Service. The initiative focused on connecting people and institutions across organisational space to create the pre-conditions for collaborative work. The paper includes evidence from an evaluation of this attempt to create a network in a complex, geographically dispersed organisation. Within the ‘theory of change’ on which the initiative was based are ideas of collaborative learning organisations, and a resistance to bureaucratic authoritarian managerialism. The paper proposes an alternative based on network theory as an alternative way of interpreting the initiative and its effects.